Tuning of Cuckoo Search Based Strategy for T-Way Testing - Abdullah, Nasser; Alsewari, Abdulrahman A.; Kamal Z., Zamli (Asian Research Publishing Network (ARPN), 2015)
Cuckoo Search Strategy (CSS) is the newly developed strategy based on the Cuckoo Search Algorithm. In order to achieve best performance, a number of parameters in the Cuckoo Search Algorithm needs to be tuned namely the nest size, the elitism probability, and the repetition. This paper describes the tuning process for Cuckoo Search Algorithm involving t-way testing, that is, by taking the standard covering array involving CA (N, 2, 46). Our initial experiment results using obtained range of parameter values of CSS demonstration that CSS able to give sufficiently competitive results compared to existing work.